GAMBARAN FAKTOR RISIKO PASIEN KANKER KOLOREKTAL DI RSUD ULIN BANJARMASIN PERIODE APRIL-SEPTEMBER 2014 - Dhia Raihana Rahdi; Agung Ary Wibowo; Lena Rosida (Berkala Kedokteran, 2015)
The incidences of colorectal cancer in a developing country such as Indonesia are thought to increase, related to some risk factors that increase the likelihood of colorectal cancer to develop. We have done a study aimed to describe the incidence of colorectal cancer based on risk factor in patients of RSUD Ulin Banjarmasin from April-September 2014. This is a descriptive study using primary data obtained through the use of questionnaire. A total of 39 samples were chosen using non randomized accidental sampling technique. The age group with the most incidence of colorectal cancer was the productive age group (15-64 years old) with as many as 79,49% of all samples. Colorectal cancer patients with a bad diet pattern were as many as 82,05% of all samples. Most of the colorectal cancer patients were diagnosed with colorectal tumor or polyp (69,72%). A total of 30 patients (76,92%) were never diagnosed with ulcerative colitis. As many as 76,93% patients were without any familial history of cancer. The lifestyles of 61,54% colorectal cancer patients were bad lifestyle. Based on the result it can be concluded that diet pattern, age, tumor history, and lifestyle had a significant distribution on the incidences of colorectal cancer. Keywords: colorectal cancer, colorectal polyp, ulcerative colitis.